2022
DOI: 10.1371/journal.pgph.0000245
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA systematic review of adolescent gender dysphoria literature: 1) Epidemiology

Abstract: It is unclear whether the research literature on adolescent gender dysphoria (GD) provides sufficient evidence to adequately inform clinical decision making. In the first of a series of three papers, this study sought to systematically review published evidence regarding: the prevalence of GD in adolescence; the proportions of natal males/females with GD in adolescence and whether this changed over time; and the pattern of age at (a) onset (b) referral and (c) assessment. Having searched PROSPERO and the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 57 publications
5
51
0
2
Order By: Relevance
“…L'accompagnement des mineurs transgenres pose des questions éthiques auxquelles il convient d'apporter des pistes de réflexion, en particulier sur les enjeux de la reconnaissance de l'autonomie de ces jeunes dans les processus de consentement et de prise de décision. < Le nombre d'enfants et d'adolescents qui expriment une non conformité entre le sexe qui leur est assigné à la naissance et leur identité de genre ressentie a fortement augmenté ces dernières années [1,2]. L'accompagnement précoce des transidentités chez les mineurs soulève des convictions aujourd'hui très controversées et engendrent des opinions divergentes chez les professionnels.…”
Section: Des Pistes De Réflexion Sur Les Enjeux éThiques De L'accompa...unclassified
See 1 more Smart Citation
“…L'accompagnement des mineurs transgenres pose des questions éthiques auxquelles il convient d'apporter des pistes de réflexion, en particulier sur les enjeux de la reconnaissance de l'autonomie de ces jeunes dans les processus de consentement et de prise de décision. < Le nombre d'enfants et d'adolescents qui expriment une non conformité entre le sexe qui leur est assigné à la naissance et leur identité de genre ressentie a fortement augmenté ces dernières années [1,2]. L'accompagnement précoce des transidentités chez les mineurs soulève des convictions aujourd'hui très controversées et engendrent des opinions divergentes chez les professionnels.…”
Section: Des Pistes De Réflexion Sur Les Enjeux éThiques De L'accompa...unclassified
“…3 Vignette (© ParaDox). 1 Lucie est un prénom d'emprunt. 2 La dysphorie de genre est le terme employé pour qualifier le sentiment d'inconfort, de détresse, de souffrances des personnes dont l'identité de genre assignée à la naissance et les caractéristiques physiques associées au sexe biologique dif-fèrent de l'identité de genre ressentie.…”
Section: Des Pistes De Réflexion Sur Les Enjeux éThiques De L'accompa...unclassified
“…In the 21st century, Western gender clinics have seen an upsurge in referrals of adolescents with features of gender dysphoria [ 27 , 28 ]. These adolescents commonly present with mental health problems and psychosocial difficulties in various domains of life [ 29 ], which is likely at least partly explained by gender dysphoria—a continuous distress—itself, or by the prejudice and discrimination related to atypical gender expression [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the last decades, a predominance of AFAB seeking medical care has been registered, showing an inversion of the previous trend (7). The age of onset of GD is difficult to estimate as in most studies only the mean age of referral at the gender services is reported, being 13.2 years (SD ±0.9), according to a recent systematic review (8).…”
Section: Introductionmentioning
confidence: 99%
“…The age of onset of GD is difficult to estimate as in most studies only the mean age of referral at the gender services is reported, being 13.2 years ( s.d. ± 0.9), according to a recent systematic review ( 8 ).…”
Section: Introductionmentioning
confidence: 99%